Образ В. Г. Короленко в творчестве удмуртских художников - Витрук Николай Васильевич (Удмуртия, 2003)
Экземпляры: (20181018) / Инвентарный номер: 29675 / Цена: 64.00 / Сис.шифр: 85.1(2Рос.Удм) / Авт.знак: В 54 / ГРНТИ: 18.31.31 / ББК: 85.1(2Рос.Удм)